Complex interplay between HIV-1 capsid and MX2-independent alpha interferon-induced antiviral factors - Bulli, Lorenzo; Kutzner, Juliane; Schaller, Torsten (Journal of virology, 2016)
Type I interferons (IFNs), including IFN-α, upregulate an array of IFN-stimulated genes (ISGs) and potently suppress Human immunodeficiency virus type 1 (HIV-1) infectivity in CD4+ T cells, monocyte-derived macrophages, and dendritic cells. Recently, we and others identified ISG myxovirus resistance 2 (MX2) as an inhibitor of HIV-1 nuclear entry. However, additional antiviral blocks exist upstream of nuclear import, but the ISGs that suppress infection, e.g., prior to (or during) reverse transcription, remain to be defined. We show here that the HIV-1 CA mutations N74D and A105T, both of which allow escape from inhibition by MX2 and the truncated version of cleavage and polyadenylation specific factor 6 (CPSF6), as well as the cyclophilin A (CypA)-binding loop mutation P90A, all increase sensitivity to IFN-α-mediated inhibition. Using clustered regularly interspaced short palindromic repeat (CRISPR)/Cas9 technology, we demonstrate that the IFN-α hypersensitivity of these mutants in THP-1 cells is independent of MX2 or CPSF6. As expected, CypA depletion had no additional effect on the behavior of the P90A mutant but modestly increased the IFN-α sensitivity of wild-type virus. Interestingly, the infectivity of wild-type or P90A virus could be rescued from the MX2-independent IFN-α-induced blocks in THP-1 cells by treatment with cyclosporine (Cs) or its nonimmunosuppressive analogue SDZ-NIM811, indicating that Cs-sensitive host cell cyclophilins other than CypA contribute to the activity of IFN-α-induced blocks. We propose that cellular interactions with incoming HIV-1 capsids help shield the virus from recognition by antiviral effector mechanisms. Thus, the CA protein is a fulcrum for the dynamic interplay between cell-encoded functions that inhibit or promote HIV-1 infection. IMPORTANCE HIV-1 is the causative agent of AIDS. During acute HIV-1 infection, numerous proinflammatory cytokines are produced, including type I interferons (IFNs). IFNs can limit HIV-1 replication by inducing the expression of a set of antiviral genes that inhibit HIV-1 at multiple steps in its life cycle, including the postentry steps of reverse transcription and nuclear import. This is observed in cultured cell systems, as well as in clinical trials in HIV-1-infected patients. The identities of the cellular antiviral factors, their viral targets, and the underpinning mechanisms are largely unknown. We show here that the HIV-1 Capsid protein plays a central role in protecting the virus from IFN-induced inhibitors that block early postentry steps of infection. We further show that host cell cyclophilins play an important role in regulating these processes, thus highlighting the complex interplay between antiviral effector mechanisms and viral survival.
Gesehen am 19.11.2018